Kesesuaian Hubungan Antara Jenis Pompa, Sumber Air, dan Tanaman yang Dialiri - Abi Prabowo; Bambang Prastowo; I.U. Firmansyah; R.H. Anasiru (agriTECH, 1996)
The research was conducted at Belawa, Wajo, South Sulawesi during dry season 011994/1995. Furrow irrigation system was used on the research. Axial type pumps were used to lilt water from creek at depths of 2 m, whereas centrifugal type pumps lifted water from the shallow well groundwater at depths of 15 m. Both type of pumps were used to irrigate soybean and maize crops with the total area for each plot of 500 m2. Maize and soybean were irrigated using furrow. Axial pump diameters and engine powers during the research were the following: 4" (6 HP), 6" (8 HP), and 8" (10 HP) respectively; while 2" (4 HP), 3" (5 HP), 4" (10 HP) for centrifugal pump. Objective of the research was to optimize benefit income from pump operations based on type of pump, irrigation type, source of water, land preparation, type of crop (s), irrigation efficiency, and yield. Results of the research shows that optimum performance among the centrifugal pump was achieved by pump diameter of 4" with optimum discharge 11.8 1/s, furrow length of 110 m, and cost of water Rp. 85.555, /season. Centrifugal pump type is suitable for soybean crop irrigation. Optimum benefit for axial type pump was obtained by PS-1 with the discharge of 35 Vs, length of furrow 180, cost of water Rp. 40.650,-/season, and suitable for maize irrigation